2007
DOI: 10.1080/10683160600822022
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle-related crime and the gender gap

Abstract: This was published as follows:has been largely restricted to crime to vehicles rather than crime by drivers or wider society. Both disciplines have, however, largely ignored the contribution of women to vehicle-related offending statistics, mirroring the pattern seen in regard to mainstream offending. This paper attempts to plug the gap by considering the relative contributions of men and women to motoring conviction data and self-report offending studies. To some extent it also does this by age, where evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Gender. Corbett (2007) reviews research on gender differences in car-related crimes and convictions as well as self-reported offenses. After pointing out the well-known overall gender gap in driving styles, resulting in a higher rate of offenses and convictions among males, she concludes that female driving styles are more heterogeneous and that there is a "ladette" subgroup of young female drivers whose driving style is more similar to that of young males.…”
Section: Individual Factorsmentioning
confidence: 99%
“…Gender. Corbett (2007) reviews research on gender differences in car-related crimes and convictions as well as self-reported offenses. After pointing out the well-known overall gender gap in driving styles, resulting in a higher rate of offenses and convictions among males, she concludes that female driving styles are more heterogeneous and that there is a "ladette" subgroup of young female drivers whose driving style is more similar to that of young males.…”
Section: Individual Factorsmentioning
confidence: 99%
“…indicate a low incidence of crime among women compared to men (Chernoff & Simon, 2000;Corbett, 2007).…”
mentioning
confidence: 93%
“…In the U.K., where the sample used in this study comes from, men were found to behave in a more risky manner than women in a variety of circumstances. For example, men risked their lives more often in everyday tasks such as crossing the street or catching a bus (Pawłowski et al 2008), took risky financial decisions (Powell and Ansic 1997), engaged in binge drinking (Emslie et al 2009) suffered minor injuries (Sumilo and Stewart-Brown 2006) and violated driving rules (Corbett 2007). The gender gap in evaluations of risk, demonstrated on samples from the U.S., mirrors the gender gap in risk taking behaviour: women evaluated potentially dangerous situations as riskier than men, were more fearful, and perceived greater danger than men when presented with the same scenarios (Harris and Miller 2000).…”
Section: Introductionmentioning
confidence: 99%